Hepatic inflammation and progressive liver fibrosis in chronic liver disease - Czaja, Albert J (Baishideng Publishing Group Co., Limited, 2014)
Chronic liver inflammation drives hepatic fibrosis, and current immunosuppressive, anti-inflammatory, and anti-viral therapies can weaken this driver. Hepatic fibrosis is reversed, stabilized, or prevented in 57%-79% of patients by conventional treatment regimens, mainly by their anti-inflammatory actions. Responses, however, are commonly incomplete and inconsistently achieved. The fibrotic mechanisms associated with liver inflammation have been clarified, and anti-fibrotic agents promise to improve outcomes as adjunctive therapies. Hepatitis C virus and immune-mediated responses can activate hepatic stellate cells by increasing oxidative stress within hepatocytes. Angiotensin can be synthesized by activated hepatic stellate cells and promote the production of reactive oxygen species. Anti-oxidants (N-acetylcysteine, S-adenosyl-L-methionine, and vitamin E) and angiotensin inhibitors (losartin) have had anti-fibrotic actions in preliminary human studies, and they may emerge as supplemental therapies. Anti-fibrotic agents presage a new era of supplemental treatment for chronic liver disease.